Ethanol Extract and Isolated Constituents from Artemisia Dracunculus Inhibit Esophageal Squamous Cell Carcinoma and Induce Apoptotic Cell Death - Hong, L.; Ying, S.-h. (Drug Research, 2015)
The objective of the present study was to examine the antitumor efficacy of the ethanol extract from Artemisia dracunculus as well as the compounds isolated from it on cultured EC‑109 esophageal squamous cell carcinoma (ESCC) cells. Apoptotic activities of the compounds were also studied using flow cytometry. EC‑109 esophageal cancer cells were treated with varying concentrations of compounds 1–7 isolated from the plant as well as the ethanol extract of Artemisia dracunculus. The cytotoxicity was evaluated by MTT assay and the apoptotic studies of the compounds were determined using flow-cytometry. Effect on mitochondrial membrane potential loss ΛΨ m induced by compounds 2 and 4 was also studied in these cells. Bioassay-guided fractionation of the ethanol extract from the shoot and root parts of Artemisia dracunculus led to the isolation of 7-methoxycoumarin (1), scopoletin (2), dracumerin (3), sakuranetin (4), elimicin (5), davidigenin (6) and 6-methoxycapillarisin (7). All the compounds as well as the extract showed mild to potent cell proliferation inhibitory activities against the esophageal cell line. Sakuranetin and 6-methoxycapillarisin were found to have the most potent effects in inhibiting the cell proliferation. The 2 potent compounds, sakuranetin and 6-methoxycapillarisin were evaluated for their effects on cell cycle phase distribution (DNA damage) as well as their effects on mitochondrial membrane potential loss ΛΨ m. Both compounds induced DNA damage as well as mitochondrial membrane potential loss in esophageal cancer cells. The study suggests that compounds, Sakuranetin and 6-methoxycapillarisin isolated from Artemisia dracunculus possess potent anticancer effects by inducing DNA damage in these cells.
Keywords: artemisia dracunculus; antitumor; apoptosis; sakuranetin; 6-methoxycapillarisin